STUDENTS’ LEARNING EXPERIENCES IN PUBLIC SPEAKING: CHALLENGES AND STRATEGIES - Nur Hidayah; Dewi Puspitasari (Program Studi Pendidikan Bahasa Inggris Institut Pendidikan dan Bahasa Invada, 2023)
This study seeks to explore the levels of self-assurance exhibited by students when engaged in public speaking following their participation in public speaking courses. The primary research questions addressed in this study are as follows: (1) What is the degree of self-confidence observed in students after completing the public speaking course? and (2) What are the difficulties encountered by students, and how do they navigate these challenges? The research employs a narrative approach, gathering data through interviews conducted with five students who have undergone public speaking courses. The collected data are subjected to analysis using three techniques, specifically data condensation, data presentation, and drawing conclusions as proposed by Miles, Huberman, and Saldana. The findings of this investigation reveal various emotions experienced by students during public speaking, including stiffness, a sense of being inarticulate, complexity, unhappiness, insecurity, nervousness, and embarrassment. Nevertheless, some participants reported improved self-assurance and enhanced confidence after completing the public speaking course. Participants also encountered challenges during public speaking, such as unclear speech, confusion, self-doubt, stage fright, difficulties in controlling expressions, and limited vocabulary. However, they devised their own strategies to overcome these challenges, such as staying calm, adopting positive thinking, practicing more, self-convincing, disregarding negative feedback, thorough topic preparation, refreshing themselves by washing their face, and offering prayers before speaking publicly. Based on the data analysis, it can be concluded that the majority of students continue to grapple with low self-confidence when speaking in public, even after completing their public speaking coursework. This study contributes valuable insights to the pedagogical process of teaching and learning public speaking within the English department.